History and future of shotgun glycomics. (9th January 2019) - Smith, David F.; Cummings, Richard D.; Song, Xuezheng
Abstract : Glycans in polysaccharides and glycoconjugates of the hydrophilic exterior of all animal cells participate in signal transduction, cellular adhesion, intercellular signaling, and sites for binding of pathogens largely through protein–glycan interactions. Microarrays of defined glycans have been used to study the binding specificities of biologically relevant glycan-binding proteins (GBP), but such arrays are limited by their lack of diversity or relevance to the GBP being investigated. Shotgun glycan microarrays are made up of structurally undefined glycans that were released from natural sources, labeled with bifunctional reagents so that they can be monitored during their purification using multidimensional chromatographic procedures, stored as a tagged glycan library (TGL) and subsequently printed onto microarrays at equal molar concentrations. The shotgun glycan microarray is then interrogated with a biologically relevant GBP and the corresponding glycan ligands can be retrieved from the TGL for detailed structural analysis and further functional analysis. Shotgun glycomics extended the defined glycan microarray to a discovery platform that supports functional glycomic analyses and may provide a useful process for ultimately defining the human glycome.